Are pocket sized ultrasound devices sufficient in the evaluation of lung ultrasound patterns and aeration scoring in pulmonary ICU patients? - Güney, Tuba (J Clin Monit Comput, 2020)
Lung ultrasound (LUS) is a practical diagnostic tool for several lung pathologies. Pocket sized USG devices (PSUDs) are more affordable, accessible, practical, and learning to use them is easier than standard ultrasound devices (SUDs). Their capability in image quality have been found as comparable with standard USG machines. Studies have been showing that these devices can be useful as much as SUDs in the evaluation of heart, abdomen, vascular structures, diaphragm and optic nerve. The aim of this study is to compare PSUD with a standard ultrasound devices (SUD) in the evaluation of LUS patterns such as alveolar, interstitial syndromes and lung aeration score (LAS). Study performed in an University Hospital Pulmonary ICU. All patients older than 18 years old were included in this study. The sector probe of SUD (Vivid-Q) and PSUD (Vscan) were used for investigation of A lines, interstitial (B lines), alveolar syndromes (consolidation, hepatisation, air bronchograms) and pleural effusion. 33 patients were included in the study. When PSUD was compared with SUD in terms of total B2 count, and LAS in the right, left and both lung, there was an agreement without proportional bias according to Bland Altman test. There was also good inter class correlation coefficient value as greater than 0.8 and 0.7 between two physicians in terms of counting of total B1, B2, total B lines and calculating of total LAS for SUD and PSUD respectively. PSUDs is a reliable and valid method for evaluation of LUS patterns like SUDs.